2002
DOI: 10.1677/jme.0.0290281
|View full text |Cite
|
Sign up to set email alerts
|

Down but not out? A novel protein isoform of the estrogen receptor alpha is expressed in the estrogen receptor alpha knockout mouse

Abstract: The mouse knockout of the estrogen receptor α (ERα) gene, known as αERKO, has been extensively used for several years to study the role and function of ERα. Residual estradiol binding capacity in uterine tissue of 5-10% raised doubts if this knockout is a genuine null mutation of ERα. Although alternatively spliced ERα mRNA variants in the αERKO mouse were reported previously, the corresponding protein isoforms have not been detected to date. Here we show that a variant ERα protein, 61 kDa in size, is expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 37 publications
2
59
0
Order By: Relevance
“…The lack of well delineated bands in lanes containing tissue proteins, with clear single bands in lanes containing recombinant proteins, is likely due to heterogeneity in ER types within tissues. This is consistent with the fact that either ER␣ or ER␤ could bind the ERE and that variants of ERs have been demonstrated in nonimmune tissues previously (24,25). Together the alteration in cytokine production during in vitro estriol treatment of immune cells and the binding of splenic protein to ERE indicated that functional ERs are expressed in murine secondary lymphoid tissues.…”
Section: Functional Er Are Present In Peripheral Immune Tissuessupporting
confidence: 86%
See 1 more Smart Citation
“…The lack of well delineated bands in lanes containing tissue proteins, with clear single bands in lanes containing recombinant proteins, is likely due to heterogeneity in ER types within tissues. This is consistent with the fact that either ER␣ or ER␤ could bind the ERE and that variants of ERs have been demonstrated in nonimmune tissues previously (24,25). Together the alteration in cytokine production during in vitro estriol treatment of immune cells and the binding of splenic protein to ERE indicated that functional ERs are expressed in murine secondary lymphoid tissues.…”
Section: Functional Er Are Present In Peripheral Immune Tissuessupporting
confidence: 86%
“…Furthermore, expression of ER␣ at the protein level in the peripheral immune system has remained poorly characterized since Western blot data were negative for specific bands of the correct size (31) while flow cytometry of immune cells was positive (29,32,33). Together these previous reports raised the question of whether the classic ER␣, vs another ER variant (24,25), was detected in immune cells by flow cytometry. Thus, we characterized ER␣ expression in secondary lymphoid tissues of mice at the RNA level by both nested RT-PCR and sequencing and at the protein level by Western blot using both Ab and ligand binding.…”
Section: Er␣ Expression At the Rna And Protein Levelsmentioning
confidence: 99%
“…The explanation of this apparent discrepancy resides most likely in the recently characterized phenotypic difference between these two mutant strains. Although the expression of the full-length 66 kDa isoform of ER␣ (p66) is abolished in ER␣-Neo Ϫ/Ϫ mice, two others splice variants lacking the AF-1 transactivator domain have been identified (p55, p46) that still possess a residual estrogen-dependent transcriptional activity (22)(23)(24). In contrast, in the mouse model of complete inactivation of ER␣ used in the present study (13,22), E 2 , even in high amounts, failed to promote DC differentiation from BM progenitors, demonstrating that ER␤ signaling could not compensate for the lack of ER␣.…”
Section: Cd11bmentioning
confidence: 99%
“…The E1 transcript encodes for a chimeric ER-␣ protein in which amino acids 92-155 of the B domain of the wild type ER-␣ protein are replaced with 7 amino acids from a small portion of the neomycin insert. This eliminates or greatly diminishes AF-1 function but not DNA or ligand binding AF-2 transactivation function (26). Although this mutant isoform of ER-␣ does promote E 2-dependent transcriptional activity, it does so at a much lower activity compared with full length ER␣66 (26,27).…”
mentioning
confidence: 97%
“…This eliminates or greatly diminishes AF-1 function but not DNA or ligand binding AF-2 transactivation function (26). Although this mutant isoform of ER-␣ does promote E 2-dependent transcriptional activity, it does so at a much lower activity compared with full length ER␣66 (26,27). Data obtained in the present study demonstrate that nonovariectomized ␣ERKO female mice are more sensitive to injurious effects of RSLϩI/R than their wt counterparts such that survival decreased from 100% in wt mice to only 40% in the ␣ERKO mice (Fig.…”
mentioning
confidence: 99%